Statue of Beethoven at Bonn - Unknown:::Creator::::::::::::; Hähnel, Ernst Julius, 1811-1891 (sculptor):::Contributor:::::::::::: (Herbert Ingram; United Kingdom; London)
Woodcut illustration of the statue of Beethoven at Bonn from a report on the Beethoven Festival on pages 101-102 of the Illustrated London News, August 16, 1845. Includes images of Hähnel's monument and the four allegorical representations of "fantasia, symphony, sacred music, and tragic music" on the base on the monument. Also includes an engraved image of the Beethoven-Haus on the Rheingasse in Bonn.